Infantile Kaposiform hemangioendothelioma in a female patient complicated with severe obstructed jaundice: a case report - Eiichiro Watanabe; Naoki Hashizume; Akihiro Yoneda; Mureo Kasahara; Genta Ozeki; Takeshi Saito; Michimasa Fujiogi; Motohiro Kano; Yuki Yamamoto; Osamu Miyazaki; Takanobu Maekawa; Noriyuki Nakano; et al. (Surgical Case Reports)
Abstract Background Kaposiform hemangioendothelioma (KHE) is a rare locally aggressive vascular neoplasm that occurs mainly in the pediatric population. KHE usually originates just underneath the skin and affects deeper tissues through infiltrative growth; however, visceral tissue involvement is quite rare. Case presentation An 8-month-old girl with jaundice and acholic stool was referred to our hospital for further evaluation of a hepatoduodenal ligament tumor. A blood examination revealed high bilirubin and liver enzyme levels, but no signs of coagulopathy. The first attempt at a diagnostic surgical procedure did not provide sufficient diagnostic information. However, the histopathological diagnosis of the cystic duct excised in the second surgery indicated KHE. Therefore, in our case, KHE was considered a cause of obstructive jaundice. Sirolimus (rapamycin) was initiated, and the patient was discharged 7 months after admission. Conclusions In cases of atypical hypervascular lesions in the abdominal cavity, especially in the pediatric population, it is important to consider the possibility of KHE, and surgical intervention with proper strategies is required for diagnosis, followed sequentially by promising treatments.